Pemilihan Software Sebagai Media Ajar Selama Masa COVID-19 di Universitas Ahmad Dahlan - Michelia Ningrum; Dian Hidayati (Universitas Pendidikan Indonesia, 2020)
This research is the evolutionary analysis of the literature on articles or writing that discusses the use of software in learning at Ahmad Dahlan University during the Covid-19 pandemic. The method used in this article is a literature study with several-page articles or articles from the world wide web, which is conducting with a narrative type (exposure) related to the topic of using the software in teaching-learning in the Covid-19 pandemic. The writer uses the data analysis technique by filtering (applies filters), based on 2019-2020. With the provisions of the title relevant to learning software, and the topic. Criteria in claims relating to software, applications, learning, campus, and pandemic or Covid-19. Thus the writer can further refine the article and match the subject matter, which is at the heart of the conflict to use as reading material and references in this article review—based on titles relevant to computer learning software and the topic. Overall, the core of this discussion is computer software that is popular in a pandemic, specially selected and used in learning at Ahmad Dahlan University.